2021
DOI: 10.1364/boe.427833
|View full text |Cite
|
Sign up to set email alerts
|

Layer-based, depth-resolved computation of attenuation coefficients and backscattering fractions in tissue using optical coherence tomography

Abstract: Structural optical coherence tomography (OCT) images of tissue stand to benefit from greater functionalization and quantitative interpretation. The OCT attenuation coefficient µ, an analogue of the imaged sample’s scattering coefficient, offers potential functional contrast based on the relationship of µ to sub-resolution physical properties of the sample. Attenuation coefficients are computed either by fitting a representative µ over several depth-wise pixels of a sample’s intensity decay, or by using previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Therefore, their analytical solutions cannot be acquired directly without knowledge of other characteristics. To address this issue, the recent studies often measured them individually while assuming the other variables to be constant 15 , 22 . These methods typically rely on accurate layer segmentation, which may fail to perform the task when there are gradual changes in tissue structure or extremely thin tissue layers, e.g., the retinal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, their analytical solutions cannot be acquired directly without knowledge of other characteristics. To address this issue, the recent studies often measured them individually while assuming the other variables to be constant 15 , 22 . These methods typically rely on accurate layer segmentation, which may fail to perform the task when there are gradual changes in tissue structure or extremely thin tissue layers, e.g., the retinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, all these computational approaches assumed a constant backscattering of the attenuated light, denoted as the backscattered fraction R(z). In theory, R(z) depends strongly on the particle size, relative refractive index, 22 and the numerical aperture (NA) of the OCT system 23 . Previous studies proved that there is a significant difference in the backscattered fraction measured from intravascular OCT images 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the adoption of μOCT allows us to describe tissue attenuation as measured by OCT as an effective parameter that does not require an estimate of the relative weight of single and multiple scattering contributions. When applying the DRE method to multiple layers with varying optical properties, the DRE method generally fails to extract the correct optical properties, unless for each layer μOCTμs only (e.g., no absorption) and pNA is a constant throughout the sample 21 . Whether or not these conditions are met in practice should ultimately be verified by experiments while the level of inaccuracy and imprecision may be estimated using simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Fiske et al 18 showed that the coefficient of variation δ D ≪ 1 already, even without preaveraging so we neglect that term in Eq. (21). See also Appendix D for further justification.…”
Section: Appendix Cmentioning
confidence: 99%